2003
DOI: 10.1079/bjn2003956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cytotoxic effects of β-sitosterol oxides and a cholesterol oxide, 7β-hydroxycholesterol, in cultured mammalian cells

Abstract: Phytosterols are plant sterols found in foods such as oils, nuts and vegetables. Phytosterols, in the same way as cholesterol, contain a double bond and are susceptible to oxidation. The objective of the present study was to assess the potential toxic effects of b-sitosterol oxides on U937 cells. The effects of increasing concentrations (0-120 mM) of b-sitosterol oxides on cellular cytotoxicity, apoptosis, antioxidant status and genotoxicity was assessed over 12, 24 and 48 h exposure periods. Following 12 h, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 38 publications
(41 reference statements)
6
60
0
Order By: Relevance
“…24 Cholesterol oxides and a mixture of b-sitosterol/campesterol oxides were examined for their cytotoxic effects on a macrophage-derived cell line (C57BL/6). All compounds exhibited similar cytotoxicity as indicated by LDH leakage, cell viability and mitochondria dehydrogenase activity, although oxyphytosterols exerted less severe effects than cholesterol oxides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Cholesterol oxides and a mixture of b-sitosterol/campesterol oxides were examined for their cytotoxic effects on a macrophage-derived cell line (C57BL/6). All compounds exhibited similar cytotoxicity as indicated by LDH leakage, cell viability and mitochondria dehydrogenase activity, although oxyphytosterols exerted less severe effects than cholesterol oxides.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 It was reported that they cause cellular damage in cultured macrophage-derived cell lines 23 and that hydroxysitosterol induces apoptosis of U937 cells, accompanied by a reduction of cellular glutathione. 24 Furthermore, numerous studies reported atherogenic 25,26 and cytotoxic properties [27][28][29][30] of cholesterol oxides, leading to apoptosis or necrosis in various cell types. 24,[31][32][33] They may also exert their effects by lowering cholesterol availability for cell membrane formation by inhibiting 3-hydroxy-methylglutaryl coenzyme A reductase (HMG-CoA reductase), a key enzyme in cholesterol synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several aspects of the possible toxic effects of POP are still to be elucidated (Tomoyori et al 2004;Lea et al 2004). Maguire et al (2003) reported that β-sitosterol oxides exhibit less severe but similar toxicity patterns to those found for COP. On the other hand, Lea et al (2004) concluded that POP do not exhibit a genotoxic potential.…”
Section: Introductionmentioning
confidence: 97%
“…1) could have toxic effects on human organisms similar to those of cholesterol oxidation products (COP) (Garcia-Cruset et al 2002). POP were shown to be accumulated in the serum and liver of mice (Tomoyori et al 2004), and to have cytotoxic effects on mammalian cells (Maguire et al 2003). POP were identified in the plasma of human subjects in amounts ranging from 4.80 to 57.2 ng/mL (Grandgirard et al 2004).…”
Section: Introductionmentioning
confidence: 99%